Regulação emocional e psicopatologias: uma revisão sistemática de literatura - Lobo, Vitória Kustódia Souza (Universidade Federal de São Carlos, 2025)
Emotion regulation is an essential psychological process involving both conscious and unconscious strategies to modulate emotional responses in the face of contextual demands. Difficulties in this process have been linked to several mental disorders, making it a relevant target for therapeutic interventions. This systematic review aimed to analyze empirical studies that investigated the impact of interventions focused on emotion regulation on regulatory skills and symptomatology associated with psychological disorders. A total of 33 studies published between January 2014 and July 2024 were selected from PubMed, CAPES, SciELO, and Google Scholar databases. Narrative synthesis revealed that most interventions produced statistically significant improvements in emotion regulation and symptom reduction, particularly in cases of depression, anxiety, personality disorders, and substance use disorders. Despite promising results, limitations included methodological heterogeneity, predominant use of self-report measures, and geographic concentration of studies in Western countries. A critical analysis of the instruments used also revealed variations in the alignment between the emotion regulation constructs adopted and the measures applied. These findings reinforce the role of emotion regulation as a transdiagnostic construct, with relevant implications for clinical practice and the development of more effective and culturally sensitive interventions.
Emotional regulation and psychopathologies: a systematic literature review
Keywords: Regulação emocional; Psicopatologia; Revisão sistemática; Transtornos mentais; Intervenções terapêuticas; Emotion regulation; Psychopathology; Systematic review; Mental disorders; Therapeutic intervention; CIENCIAS HUMANAS::PSICOLOGIA